Analysis of goal scoring that discriminated between winning and losing team in FIFA Futsal World Cup 2016 / Muhammad Iftiqar Ahmad Termizi - Ahmad Termizi, Muhammad Iftiqar (2018)
In the current study, total of 43 videos were analysed in order to determine any difference in term of goal scoring in FIFA Futsal World Cup 2016. Goal scoring was the climax and one of the most important indicators in any sport. Total of 39 indicators were used and Mann Whitney Test was used to determine the difference between winning and losing team. The objective of this study is to investigate the differences of winning and losing teams in terms of goal scoring and other selected performance indicator that related with goal scoring. The results shows the significant on curl shot and driven shot are .279±.477 (Z=, p<0.05) and 1.291±1.3879 (Z=, p<0.05). For the number of touches, 0 and I are the only significant results which show 2.244±1.8783 (Z=, p<0.05) and 0.640±0.8665 (Z=, p<0.05). For crossing, only the left crossing is significant which is 0.314±0.5371 (Z=, p<0.05). Passing are the where most significant results are found. They are inside foot (1.872±1.578) (Z=, p<0.05), outside foot (.267±.538) (Z=, p<0.05), through ball (.385±. 706) (Z=, p<0.05), lob (.361±.612) (Z=, p<0.05), backheel (.047±.212) (Z=, p<0.05) and sole passing (.093±.292) (Z=, p<0.05). Lastly, area shot at the goal post that produce a goal which were area A (.395±.656) (Z=, p<0.05), C (.430±.660) (Z=, p<0.05), D (.814±1.012) (Z=, p<0.05), E (.744±.857) (Z=, p<0.05) and F (.919±1.066) (Z=, p<0.05). It can be concluded that in this current study, the important indicators that being used in the tournament were found significantly different between winning and losing team.